(untitled) (Fiep Bulletin - online, 2011)
The present article has as objective to detach which the benefits of the offer of the dance to the pupils in the pertaining to school environment, that is the importance of the dance as curricular element. For such end, existing literature on the subject was analyzed. The dance will collaborate of form to make possible new ways of intervention in the education them children, contributing for the questions of the anthropocentric vision that promotes the isolation and the incommunicability, capable to spoil the sociability forms . It has been broken thus of an education parted in values that promote the understanding and the autonomy, an education worried about the life, the proper body and the body of the other, configured possibilities of new forms of being, living and putting into motion themselves. Finally, it will be possible to have interventions in the education of form to problematical segregators’ conceptions of body, movement, culture and of the proper knowledge. It will spread out an education that considers that the body is part of the world and in an ethical and aesthetic relation, that exceeds the instrumental rationality and the reductive logics of the processes of construction of the knowledge.